Sexploitation and Non-marital Sex Normalization Discourse in USS Feed - Muhammad Dicka Ma'arief Alyatalatthaf; Heppy New Year Haloho (Jurnal Ilmu Komunikasi)
Some Indonesian media outlets that produce sex education videos exploit sexuality to attract viewers instead. This research aims to identify the sexual commodification and non-marital sex normalization in "USS Feed–#SEXED". The research uses van Dijk’s critical discourse analysis. Data collection techniques include documentation, observation, and intertextual literature. The result shows sexploitation is manifested through the objectification of sexuality through female respondents' sexual experiences and the exploitation of erotic fantasies through demonstrations of sex equipment. Meanwhile, the normalization of non-marital sex discourse can be seen in the normalization construction of consent-based sex and safe sex by only using condoms.